Sex differences in the association of measures of sexual maturation to common toxicants: Lead, dichloro-diphenyl-trichloroethane (DDT), dichloro-diphenyl-dichloroethylene (DDE), and polychlorinated biphenyls (PCBs) - Casey N. West; Lawrence M. Schell; Mia V. Gallo (Taylor & Francis Group, 2021)
Many studies of human toxicant exposure examine the hypothesis that human sexual maturation can be affected through endocrine disruption. Within this body of literature there is significant variation in the findings. Variation may be related to the differential effects by toxicants between males and females as well as variation in sample size, toxicant levels, and the timing of exposure. We review sexual maturation outcomes between males and females when exposed to lead, dichlorodiphenyldichloroethylene (DDE), dichloro-diphenyl-trichloroethane (DDT), and polychlorinated biphenyls (PCBs) using a systematic process to gather peer-reviewed studies published from January 1994 through December 2019 on the NCBI website's PubMed search engine. The review includes 34 studies, some comprised of multiple analyses, to compare effects on sexual maturation by sex. The analysis shows that both boys and girls have delayed sexual maturation in relation to lead exposure. There are differences in the direction of effects associated with DDE/DDT and PCB exposure in boys and girls. PCBs exist as congeners of many structural forms, and that variation is considered in this review. Dioxin-like and non-dioxin-like PCBs exposure directionality differed between boys and girls as well. Future investigations into the basis of sex variation in DDE/DDT and PCB relationships to sexual maturation are warranted.